2011
DOI: 10.1007/s11192-011-0414-x
|View full text |Cite
|
Sign up to set email alerts
|

Patent co-citation networks of Fortune 500 companies

Abstract: This paper provides an overview of the progression of technology structure based on patent co-citation networks. Methods of patent bibliometrics, social network analysis and information visualization are employed to analyze patents of Fortune 500 companies indexed in Derwent Innovations Index, the largest patent database in the world. Based on the co-citation networks, several main technology groups are identified, including Chemicals, Petroleum Refining, Motor Vehicles, Pharmaceuticals, Electronics, etc. Rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…This map, based on the multidimensional scaling algorithm, categorised the companies into six major clusters, namely semiconductor, computer peripheral equipment, scanner, notebook/monitor, system, and IC design/packaging. Wang, Zhang, and Xu (2011) showed the patent co-citation networks of Fortune 500 companies using a bibliometric mapping technique. It was found that ICT companies most actively referred to the patents of other companies within the same sector during the 1990s while the chemical companies were also found to be most active as intermediaries in the same period.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This map, based on the multidimensional scaling algorithm, categorised the companies into six major clusters, namely semiconductor, computer peripheral equipment, scanner, notebook/monitor, system, and IC design/packaging. Wang, Zhang, and Xu (2011) showed the patent co-citation networks of Fortune 500 companies using a bibliometric mapping technique. It was found that ICT companies most actively referred to the patents of other companies within the same sector during the 1990s while the chemical companies were also found to be most active as intermediaries in the same period.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…5 However, in this previous study, detailed technological elements and their interrelationships have not been uncovered despite their importance in implementing a certain technology (Shapiro 2001;Cockburn, Macgarvie, and Müller 2010;Parr and Smith 2010). To address this issue, the bibliometric mapping technique can be applied because this technique effectively converts voluminous text information into one snapshot in consideration of the interrelationships among words (Schmoch and Schnoring 1994;Huang, Chiang and Chen 2003;Van and Eck and Waltman 2010;Wang, Zhang, and Xu 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One of their conclusions is that they cannot detect substantial progress in European research integration other than the common global trend. Wang, Zhang, and Xu (2011) take the entire domain of technology as a starting point and analyze how the developments in the different fields of technology are related at the firm level. They use patent co-citation networks to identify the technological links between 500 important companies.…”
Section: Further Diversification Of Technology Mappingmentioning
confidence: 99%
“…O destaque a termos associados com patentes (patents) (Baron & Delcamp, 2012;Frietsch & Schmoch, 2010;Makkonen & van der Have, 2013;Wang, Zhang, & Xu, 2011), pesquisa e desenvolvimento (research and development) (Czarnitzki et al, 2011;Porter, 2007a;Watts & Porter, 2003), e indicadores compostos (composite indicators) (Grupp & Schubert, 2010;Mahroum & Alsaleh, 2012Paas & Poltimäe, 2012) justifica-se pelo fato de que, tradicionalmente, os dados associados aos dois primeiros termos são utilizados como principais indicadores de inovação. Mais recentemente, entretanto, diversas iniciativas passaram a adotar o uso de indicadores compostos.…”
Section: Figura 3 -Representação De Ocorrência Das Palavras-chave Apóunclassified